Strong ring extensions andphi-pseudo-valuation rings - Badawi, Ayman (2006)
In this paper, we extend the concept of strong extensions of domains to the context of (commutative) rings with zero-divisors. We show that the theory of strong extensions of rings resembles that of strong extensions of domains.